2015
DOI: 10.1038/ncomms6988
|View full text |Cite
|
Sign up to set email alerts
|

Gd-metallofullerenol nanomaterial as non-toxic breast cancer stem cell-specific inhibitor

Abstract: The contemporary use of nanomedicines for cancer treatment has been largely limited to serving as carriers for existing therapeutic agents. Here, we provide definitive evidence that, the metallofullerenol nanomaterial Gd@C82(OH)22, while essentially not toxic to normal mammary epithelial cells, possesses intrinsic inhibitory activity against triple-negative breast cancer cells. Gd@C82(OH)22 blocks epithelial-to-mesenchymal transition with resultant efficient elimination of breast cancer stem cells (CSCs) resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
115
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(117 citation statements)
references
References 53 publications
1
115
1
Order By: Relevance
“…This therefore provides a perfect example of a specific nanoscale interaction between a synthetic nanoparticle and a biological receptor (protein) that can be harnessed for therapeutic gain. More recently, Liu et al (59) reported that Gd@C 82 (OH) 22 are essentially nontoxic to normal mammary epithelial cells, while these nanoparticles possess intrinsic inhibitory activity against triple-negative breast cancer cells. Moreover, the authors provided evidence that the nanoparticles specially inhibited so-called breast cancer stem cells, resulting in the abrogation of tumor initiation and metastasis (59).…”
Section: The Other Side Of the Coin: Nanomedicinementioning
confidence: 99%
See 1 more Smart Citation
“…This therefore provides a perfect example of a specific nanoscale interaction between a synthetic nanoparticle and a biological receptor (protein) that can be harnessed for therapeutic gain. More recently, Liu et al (59) reported that Gd@C 82 (OH) 22 are essentially nontoxic to normal mammary epithelial cells, while these nanoparticles possess intrinsic inhibitory activity against triple-negative breast cancer cells. Moreover, the authors provided evidence that the nanoparticles specially inhibited so-called breast cancer stem cells, resulting in the abrogation of tumor initiation and metastasis (59).…”
Section: The Other Side Of the Coin: Nanomedicinementioning
confidence: 99%
“…More recently, Liu et al (59) reported that Gd@C 82 (OH) 22 are essentially nontoxic to normal mammary epithelial cells, while these nanoparticles possess intrinsic inhibitory activity against triple-negative breast cancer cells. Moreover, the authors provided evidence that the nanoparticles specially inhibited so-called breast cancer stem cells, resulting in the abrogation of tumor initiation and metastasis (59). They found that under hypoxic conditions in the tumor microenvironment, crucial surface modifications of the Gd-metallofullerenol occurred, which promoted tumor uptake, enhancing the elimination of cancer stem cells.…”
Section: The Other Side Of the Coin: Nanomedicinementioning
confidence: 99%
“…110,111 Liu et al recognised that, while sharing the same number of hydroxyl groups, Gd@C 82 (OH) 22 outperformed C 60 (OH) 22 in the inhibition of breast cancer metastasis. 112 This is a good demonstration of the effect of the incarcerated species in EMFs on their reactivity, structure and subsequent function. Chen et al found the antineoplastic activity of Gd@C 82 (OH) 22 was considerably greater than that of commonly used cis-platin, thus adding weight to the claim for fullerenes to be used as chemotherapeutic agents.…”
Section: Chemotherapymentioning
confidence: 99%
“…For example, graphene oxide can selectively induce CSC differentiation by inhibiting multiple key pathways for CSC self-renewal including WNT, Notch and STAT-signaling. Since graphene oxide is non-toxic, this therapeutic strategy is promising for CSC eradication [106]. The metallofullerenol nanomaterial, Gd@C82(OH)22, can block epithelialto-mesenchymal transition with resultant efficient elimination of breast CSCs, potentially through a bi-potent inhibition of HIF-1α and TGF-β activities [107].…”
Section: Targeting Lscs By Nanomedicinementioning
confidence: 99%